International order and the politics of disaster - Watson, Scott D. 1974- (Routledge, Taylor & Francis Group, 2020)
"In this indispensable and comprehensive text, Scott D. Watson critically examines the current understanding of international order that underpins international disaster management and disaster diplomacy. Based on empirical analysis of the three international 'disaster management regimes' (disaster relief, disaster risk reduction, and disaster migration) and case studies of disaster diplomacy in the United States, Egypt and China, Watson argues that international disaster management and disaster diplomacy are not simply efforts to reduce the impact of disasters or to manage bilateral relations, but to reinforce key beliefs about the larger international order. Challenging the conventional understandings of disasters as natural, as an exogenous shock, or as an unintended and accidental outcome of the current order, this text shows how the ideological foundations of the current heterogenous international order produce recurrent disasters. International Order and the Politics of Disaster will be a vital source for undergraduate or graduate students interested in international responses to disasters and complex humanitarian emergencies, forced migration and displacement, as well as climate change and development"--